The impact of genetic counselors' use of facilitative strategies on cognitive and emotional processing of genetic risk disclosure for Alzheimer's disease. Issue 5 (May 2018) - Guan, Yue; Roter, Debra L.; Wolff, Jennifer L.; Gitlin, Laura N.; Christensen, Kurt D.; Roberts, J.Scott; Green, Robert C.; Erby, Lori H.
Highlights: GCs used more cognitive relative to emotional facilitative strategies. Patients and companions engaged in more cognitive relative to emotional processing. Facilitation was associated with both emotional and cognitive processing of AD risk. Abstract: Objectives: To determine the impact of genetic counselor (GC) communication on cognitive and emotional processing of Alzheimer's disease (AD) risk information during discussions with patients with clinical diagnoses of mild cognitive impairment and their companion. Methods: 79 recordings and transcripts of AD risk disclosure sessions collected as part of the fourth REVEAL Trial were coded using the Roter Interaction Analysis System (RIAS) and the Linguistic Inquiry Word Count (LIWC). Multilevel analyses were used to determine the association between GCs' use of communication facilitation strategies and patient and companion use of words indicative of cognitive and emotional processing. Results: GC used somewhat more cognitive (14%) than emotional (10%) facilitation strategies. Both patients and companions used more words indicative of cognitive (18% and 17%) than emotional (6% and 5%) processing. GC use of facilitative strategies and patient and companion use of cognitive and emotional processing words were significantly associated in both unadjusted and adjusted models (all p-values < 0.01). Conclusions: GCs' use of facilitative strategies assist in cognitive and emotional processing in a way that may be linked to therapeutic benefit. Practice implications: These findings highlight mechanisms through which GCs may assist patients and companions to better understand and cope with risk information.